#TITLE_ALTERNATIVE# - PRABOWO , BAYU
In various literatures high strength concrete is described as concrete with minimum strength of 41 MPa, which possessed high strength, high durability and low permeability, in order to achieve optimum and efficient construction concretes. Such concretes are usually manufactured by adding relatively expensive silica fume admixture, hence making an expensive and limitedly used concrete. One of the most affordable methods to achieve high strength concretes is by administering low water-cement ratio in concrete mixtures. However low water-cement ratio tends to lower the concrete mixture's workability, eventually resulting in more complicated manufacturing or lower quality concretes. This research is aimed towards the manufacture of high strength concretes out of normal concrete mixtures (without silica fume) by introducing several variations of compaction methods. A second objective is to observe the potential use of rice husk ash as an alternative to silica fume in constituting for the majority of cement weight in concretes. To observe the effect of different compaction methods on the concrete strength produced, compression test were carried out to cylindrical specimens with a height/diameter ratio of 2. The result of the compression test showed that compaction with pressure of 200 Bar increased the strength of concretes from 16,7 to 33,4 MPa. Further strength increase was observed when the compaction method was changed to vibrate the mixture and this resulted in concrete strength as high as 44,1 ± 0,5 MPa. The combination of pressure and vibration resulted in the decrease of the average concrete strength around 14,6 MPa. The experiment was then continued by varying the water-cement ratio and substituting some of the cement with ground rice husk ash. The substitution resulted in an increase of strength from 44,1 ± 0,5 up to 52,8 ± 2,0 MPa at water-cement ratio of 0,22, but at 0,25, the strength decreased from 65,8 ± 0,3 to 53,7 ± 1,9 MPa. An explanation to this phenomenon has been proposed in the analysis but further elaboration may be required.